PREDICTING CONSUMER BEHAVIOR USING NEUROMARKETING TOOLS (Marketing Journal, 2025)
Тhis article provides an in -depth exploration of the application of neural networks in marketing, with a particular focus on predicting consumer behavior in real time. In today’s fast -paced digital economy, marketers are tasked with analyzing vast and conti nuously evolving datasets to keep up with shifting consumer preferences. Traditional approaches —such as surveys, focus groups, or statistical modeling —often fall short, as they capture behavior only after the fact and lack the agility to respond to rapid changes. Neural networks, however, leverage a brain -inspired architecture of interconnected nodes to uncover hidden patterns within data, enabling highly accurate predictions of consumer actions, such as purchases or interactions with advertisements, preci sely as they occur. The authors elaborate on the transformative benefits of neural networks for marketing professionals. These include the ability to craft highly personalized customer experiences, optimize advertising campaigns through real -time targeting, and foster greater customer loyalty by delivering relevant interactions at critical moments.
Keywords: Neuromarketing; consumer behavior; fMRI; EEG; eye -tracking; emotional triggers; marketing strategies; subconscious decision -making; ethical aspects; digital technologies